Measurement of the top quark pair production cross section in the all-jets decay channel - Abbott, B; Abolins, M; Abramov, V; Acharya, B; Adam, I; Adams, D; Adams, M; Ahn, S; Alves, G; Amos, N; Anderson, E; Baarmand, M; et al. (1999)
We present a measurement of tt̄ production in p p̄ collisions at √s = 1.8 TeV from 110 pb-1 of data collected in the all-jets decay channel with the D0 detector at Fermilab. A neural network analysis yields a cross section of 7.1 ± 2.8(stat) ± 1.5(syst) pb at a top quark mass (m,) of 172.1 GeV/c2. Using previous D0 measurements from dilepton and single lepton channels, the combined DO result for the tt̄ production cross section is 5.9 ± 1.2(stat) ± 1.1(syst) pb for mt = 172.1 GeV/c2. © 1999 The American Physical Society.